Fuzzy Assessment of Steel Deck Pavement for Long Suspension Bridge of the Fourth Nanjing Yangtze River Bridge - Jinyu Zong; Keqiang Zhang; Binggen Zhan; Rui Ma (Advances in Civil Engineering)
The Fourth Nanjing Yangtze River Bridge (the Fourth Bridge) with the main span of 1418 m is the largest three-span suspension bridge in China and the third largest in the world. The service circumstance of steel deck pavement on the Fourth Bridge is complex and severe, so that the scheme evaluation for steel deck pavement is a huge program. To rapidly and comprehensively evaluate the schemes for pavement, a fuzzy evaluation method was introduced in this paper. A three-level logical assessment structure including 21 basic impact factors was built according to analytic hierarchy process (AHP), and the weight for each judgment matrix was determined by the Delphi method. Consequently, a fuzzy evaluation theory was used to value each scheme to propose the optimal one. Based on this method, four pavement schemes were evaluated to choose the optimal one, and the performance of the optimal scheme was highly corresponding to the practical engineering practice. The fuzzy evaluation method can supply a theoretical support to fast determine the scheme for long-span steel deck pavement.